Dynamics of Soluble Thrombomodulin and Circulating miRNAs in Patients with Atrial Fibrillation Undergoing Radiofrequency Catheter Ablation - Namino, Fuminori (Clin Appl Thromb Hemost, 2019)
Atrial fibrillation (AF) is the most common cardiac arrhythmia in the world and has a high risk of thromboembolism. The most effective approach, catheter ablation, requires evaluation by electrocardiography. The aim of our study was to investigate novel clinical markers that predict restoration of sinus rhythm (SR) after catheter ablation. Seventy-eight consecutive patients with AF underwent catheter ablation and were separated into 2 groups: restored SR and recurrent AF. The levels of 4 blood proteins (serum or plasma) and 3 mature microRNAs (miRNAs) and their primary miRNAs (pri-miRNAs) in serum were measured before and after ablation, and the associations between each parameter were analyzed statistically. Soluble thrombomodulin (s-TM) and plasminogen activator inhibitor-1 (PAI-1) levels increased above baseline after ablation in both the restored SR (s-TM 11.55 [2.92] vs 13.75 [3.38], P < .001; PAI-1 25.74 [15.25] vs 37.79 [19.56], P < .001) and recurrent AF (s-TM 10.28 [2.78] vs 11.67 [3.37], P < .001; PAI-1 26.16 [15.70] vs 40.74 [22.55], P < .001) groups. Levels of C-reactive protein and asymmetric dimethylarginine were not significantly changed. Pri-miR-126 levels significantly decreased after ablation in the recurrent AF group, but the other miRNAs and pri-miRNAs did not. The measurement of s-TM and pri-miR-126 in blood was a useful tool to reflect the condition of AF patients with catheter ablation.